1646. Combined Resistance Analyses From Phase 2b Studies of Presatovir Treatment in RSV-Infected Adults. (26th November 2018) - Porter, Danielle; Guo, Ying; Perry, Jason; Gossage, David; Watkins, Timothy; Chien, Jason; Jordan, Robert
Abstract: Background: Presatovir is an oral respiratory syncytial virus (RSV) fusion inhibitor in development for the treatment of RSV infection. Results from a healthy volunteer challenge study show that presatovir significantly reduced RSV viral load and clinical signs and symptoms. Here we present combined resistance analyses from 4 phase 2b studies in naturally RSV-infected adults. Methods: RSV RNA was isolated from nasal swabs collected at baseline and postbaseline in studies GS-US-218-0108, GS-US-218–1502, GS-US-218–1227, and GS-US-218–1797. Full-length RSV fusion (F) gene was PCR amplified and population sequencing was performed. Results: Of 233 presatovir-treated adults in the efficacy analyses, post-baseline resistance-associated substitutions were detected in 18 (7.7%) subjects. Frequencies of resistance development varied by study (Table 1). Resistance substitutions known to confer high-level (>200 fold) reduced susceptibility to presatovir detected in >1 subject were: T400I ( n = 6), S398L ( n = 3), L141F ( n = 2), and F140I ( n = 2) in F. Subjects with resistant virus had less viral load reduction than presatovir-treated subjects without resistant virus. Resistance development did not impact clinical outcomes. In study GS-US-218-0108, subjects with lymphopenia (<200 cells/μL) at baseline were significantly more likely to develop resistance substitutions. Conclusion: Presatovir treatment resulted in varying rates of resistance development across 4 phase 2b studies. Resistance development impacted virologic response without affecting clinical outcomes. Differences among study populations and dosing regimens may have influenced rates of resistance development. Disclosures: D. Porter, Gilead Sciences, Inc.: Employee and Shareholder, Salary and stocks. Y. Guo, Gilead Sciences, Inc.: Employee and Shareholder, Salary and stocks. J. Perry, Gilead Sciences, Inc.: Employee and Shareholder, Salary and stocks. D. Gossage, Gilead Sciences, Inc.: Employee and Shareholder, Salary and stocks. T. Watkins, Gilead Sciences, Inc.: Employee and Shareholder, Salary and stocks. J. Chien, Gilead Sciences, Inc.: Employee and Shareholder, Salary and stocks. R. Jordan, Gilead Sciences, Inc.: Employee and Shareholder, Salary and stocks.